Microzonation of Soil Amplification Based on Microtremor, Spt and Cptu Data in Bandung Basin - Anggun Mayang Sari; Eko Soebowo; Afnindar Fakhrurrozi; Arifan Jaya Syahbana; Adrin Tohari (Indonesian Institute of Sciences, 2019)
Bandung Basin consists of Sunda-Tangkuban Perahu volcanic deposit that is made of lake sediment and an alluvial fan with fine to coarse-grained materials such as clay, silt and sand. The area is surrounded by several earthquake sources such as the Lembang, Cimandiri, and Baribis Faults. Therefore, it is important to understand soil dynamic problems with respect to seismic sources and soil properties. This research aims to investigate velocity amplification of the Bandung Basin using microtremor measurements and site classification based on the Standard Penetration Test (SPT) and Cone Penetrometer Test (CPTu). Velocity amplification was analyzed using the horizonal to vertical H/V spectral ratio, and site classification was determined using and values. Microzonation maps were developed using Geographical Information System (GIS) to determine the correlation between soil velocity amplification and site class. The results revealed that velocity amplification levels in the Bandung Basin vary with a range of 1.3 to 26.5. Site classification ranges from very dense soil and hard rock (class C), stiff soil (class D) to soft clay soil (class E). Site class E dominates the southeast part of the Bandung Basin with a high value of soil amplification. This scientific information is critical for further spatial planning focusing on infrastructure and residential building. Cekungan Bandung berasal dari endapan vulkanik Sunda-Tangkuban Perahu yang terdiri dari sedimen danau dan kipas aluvial dengan material berbutir halus hingga kasar seperti lempung, lanau, dan pasir. Daerah ini juga dikelilingi oleh beberapa sumber gempa yakni sesar Lembang, Cimandiri, dan Baribis. Oleh karena itu masalah dinamika tanah yang dipengaruhi oleh sumber seismik dan sifat tanah perlu menjadi perhatian. Tujuan penelitian ini adalah untuk mengetahui amplifikasi kecepatan tanah di wilayah cekungan Bandung dengan menggunakan alat mikrotremor dan metode site classification berdasarkan uji SPT dan CPTu. Amplifikasi kecepatan dianalisis menggunakan perbandingan rasio spektral H/V dan site classification yang diperoleh dengan menggunakan nilai dan . Peta mikrozonasi disusun menggunakan teknik Sistem Informasi Geografis (SIG) untuk menentukan korelasi amplifikasi tanah dan site class tanah. Hasil penelitian menunjukkan bahwa tingkat amplifikasi kecepatan di Cekungan Bandung bervariasi, berkisar 1,3 hingga 26,5. Site classification berkisar dari tanah yang sangat padat dan batuan keras (kelas C), tanah kaku (kelas D) hingga tanah lempung lunak (kelas E). Hasil penelitian menunjukkan site class E mendominasi bagian selatan Cekungan Bandung dengan nilai amplifikasi tanah yang tinggi. Informasi ilmiah ini diperlukan untuk perencanaan tata ruang kedepannya, dengan fokus pada infrastruktur dan bangunan tempat tinggal.